MORAL MESSAGE IN ADVERTISEMENT "لا ينسانا الله" BY ZAIN GROUP: ROLAND BARTHES SEMIOTIC ANALYSIS - Hamas, Marisa Salsabila; Masadi, M. Anwar (Annual International Conferences on Language, Literature, and Media, 2021)
The aim of this study is to describe the moral message contained in the advertisement entitled "لا ينسانا الله" by Zain Group in 2020 using Semiotic theory of Roland Barthes. This research is a qualitative descriptive study. Data collection was done by watching, taking notes. The researchers used persistence data triangulation, and discussion to test the data validity. The analysis took four scenes in the video and each scene had some slides respectively. The result of the study covers two stages of meaning. First, the meaning of denotation and connotation in each scene obtained from the symbols contained in the images and writings in the video advertisement. Second, the sign in the first stage will change its position to become a marker in the second stage of meaning, so that researchers can decipher the meaning of mythology which produces a description of the moral message. The moral message in this advertisement reflects the life of the world community today in the face of a new disease outbreak, COVID-19. Thus, this research can explain the audience about what is contained in it, and increase the audience's appreciation for seeing it.